2020
DOI: 10.1128/aem.01920-20
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Centric Metagenomic Insights into the Impact of Alkaline/Acid and Thermal Sludge Pretreatment on the Microbiome in Digestion Sludge

Abstract: Pre-treatment of waste activated sludge (WAS) is an effective way to destabilize sludge floc structure and release organic matter for improving sludge digestion efficiency. Nonetheless, impacts of WAS pre-treatment on digestion sludge microbiomes, as well as mechanistic insights into how sludge pre-treatment improve digestion performance, remain elusive. In this study, genome-centric metagenomic approach was employed to investigate the digestion sludge microbiome in four sludge digesters with different feeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Those compounds reduce the feedstock biodegradability and correspondingly impact microbial communities [11,12]. It was found that the Shannon diversity of microbial communities was significantly decreased after the inclusion of THP during anaerobic digestion [12,19,20], which was potentially due to the sterilization effect of THP on indigenous microbes [21]. The structure of the methanogens' community also showed adaptation to TH pretreated substrate during biogas production.…”
Section: Introductionmentioning
confidence: 99%
“…Those compounds reduce the feedstock biodegradability and correspondingly impact microbial communities [11,12]. It was found that the Shannon diversity of microbial communities was significantly decreased after the inclusion of THP during anaerobic digestion [12,19,20], which was potentially due to the sterilization effect of THP on indigenous microbes [21]. The structure of the methanogens' community also showed adaptation to TH pretreated substrate during biogas production.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-resolved metagenomics was firstly applied in 2004 from low microbial diversity environment (Tyson et al 2004), followed by a series of initiations such as Earth Microbiome Project (EMP) and the European Nucleotide Archive (ENA) which enabled us to unravel the microorganisms on a global scale (Thompson et al 2017). For example, the latest report from EMP projects revealed more than 52,000 Metagenomic Assembled Genomes (MAGs) on species level (Amid et al 2020, Nayfach et al 2020), consisting a wide range of samples from environments with medium to high level of microbial complexities, such as human (Pasolli et al 2019, Almeida et al 2021), freshwater (Ali et al 2020), marine (Tully et al 2018, Reji et al 2020), engineered environment (Ransom-Jones et al 2017, Liang et al 2020) and soil (Kroeger et al 2018, Nascimento Lemos et al 2020), etc. Such studies implementing genome-resolved metagenomic approaches have largely expanded branches of microorganisms on tree of life (Hug et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Shotgun metagenomic sequencing has helped to reveal the diversity of microbial communities in natural habitats [ 15 ] and in engineered environments such as composting [ 1 , 16 ] or sludge digesters [ 17 ]. New methods and computational tools now allow the recovery of metagenome-assembled genomes (MAGs) from complex ecosystems [ 18 23 ].…”
Section: Introductionmentioning
confidence: 99%